(untitled) (PANGEEA, 2025)
It has somehow become a truism the fact that when a client is satisfied by the product or a service that he buys from a company, he becomes loyal to this product and automatically to the respective company. Because the satisfaction of an individual is associated with his loyalty for a specific service or product (Gholipour & Einolahzadeh, 2018; Cai&Chi, 2018; Shahsavar& Sudzina, 2017), the university should be preoccupied about the relationship between student satisfaction and their institutional loyalty. If the students are satisfied with the quality of the educational services offered by a certain specialization, they will also suggest to relatives, acquaintances or friends to follow the studies within the that specialization and educational institution. In the scientific literature, the definitions on customer satisfaction are divided into two categories (Grigoroudius & Siskos, 2010): the satisfaction as a result, an emotional response related to the gained experience from the process of purchasing specific products / provided services / due to a certain model of behaviour induced by sellers and the satisfaction as a process, an evaluation response based on the experience regarding to the effective quality of a product.